A z = 2.5 protocluster associated with the radio galaxy MRC 2104-242: star formation and differing mass functions in dense environments - Cooke, E.A.; Hatch, Nina A.; Muldrew, S.I.; Rigby, E.E.; Kurk, J.D. (Oxford University Press, 2014)
We present results from a narrow-band survey of the field around the high-redshift radio galaxy MRC 2104−242. We have selected Hα emitters in a 7 arcmin2 field and compared the measured number density with that of a field sample at similar redshift. We find that MRC 2104−242 lies in an overdensity of galaxies that is 8.0 ± 0.8 times the average density of a blank field, suggesting it resides in a large-scale structure that may eventually collapse to form a massive cluster. We find that there is more dust obscured star formation in the protocluster galaxies than in similarly selected control field galaxies and there is tentative evidence of a higher fraction of starbursting galaxies in the denser environment. However, on average we do not find a difference between the star formation rate (SFR)–mass relations of the protocluster and field galaxies and so conclude that the SFR of these galaxies at z ∼ 2.5 is governed predominantly by galaxy mass and not the host environment. We also find that the stellar mass distribution of the protocluster galaxies is skewed towards higher masses and there is a significant lack of galaxies at M < 1010M_ within our small field of view. Based on the level of overdensity we expect to find ∼22 star-forming galaxies below 1010M_ in the protocluster and do not detect any. This lack of low-mass galaxies affects the level of overdensity which we detect. If we only consider high-mass (M > 1010.5M_) galaxies, the density of the protocluster field increases to ∼55 times the control field density.